Folic acid use and major congenital malformations in offspring of women with epilepsy: a prospective study from the UK Epilepsy and Pregnancy Register. Issue 5 (31st October 2008) - Morrow, J I; Hunt, S J; Russell, A J; Smithson, W H; Parsons, L; Robertson, I; Waddell, R; Irwin, B; Morrison, P J; Craig, J J
Abstract : Objective: In the general population, folic acid supplementation during pregnancy has been demonstrated to reduce the frequency of neural tube defects (NTDs) and other major congenital malformations (MCMs). It is recommended that women with epilepsy contemplating pregnancy take supplemental folic acid because of the known antifolate effect of some antiepileptic drugs (AEDs). Here the aim was to determine the effectiveness of this practice. Methods: This study is part of a prospective, observational, registration and follow-up study. Suitable cases are women with epilepsy who become pregnant and who are referred before outcome of the pregnancy is known. The main outcome measure is the MCM rate. Outcomes were analysed against folic acid exposure, malformation type and drug group for the most commonly used monotherapy AEDs. Results: In 1935 cases reported to have received preconceptual folic acid, 76 MCMs (3.9%; 95% CI 3.1 to 4.9) and eight NTDs (0.4%; 95% CI 0.2 to 0.8) were identified. For 2375 women who were reported to have received folic acid but not until later in the pregnancy (n = 1825) or not at all (n = 550), there were 53 outcomes with an MCM (2.2%; 95% CI 1.7 to 2.9) and eight NTDs (0.34%; 95% CI 0.2 to 0.7). Conclusions: The study supports the view that extrapolation from studies carried out in the general population to groups of women with epilepsy may be questionable. It may be that the increased risk of MCM recorded in this group occurs through mechanisms other than that of folic acid metabolism.